2021
DOI: 10.1177/23971983211016196
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of dimethyl fumarate in pulmonary arterial hypertension associated with systemic sclerosis

Abstract: Introduction: Given the poor treatment options for pulmonary arterial hypertension–associated systemic sclerosis patients, we sought to determine clinical safety and efficacy of dimethyl fumarate, an Nrf2 agonist, and the effects on biomarkers of oxidative stress on pulmonary arterial hypertension–associated systemic sclerosis in an exploratory interventional clinical trial. Objectives: The primary objectives were to assess the safety and efficacy of treatment with dimethyl fumarate in patients with pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The subjects in the DMF group showed a non-significant reduction in decline in the 6MWD test, however the study was not effectively powered to assess for efficiency. Thus, Nrf2 remains a therapeutic target that needs further studies assessing its role in the treatment of PAH [ 87 ].…”
Section: Novel Therapiesmentioning
confidence: 99%
“…The subjects in the DMF group showed a non-significant reduction in decline in the 6MWD test, however the study was not effectively powered to assess for efficiency. Thus, Nrf2 remains a therapeutic target that needs further studies assessing its role in the treatment of PAH [ 87 ].…”
Section: Novel Therapiesmentioning
confidence: 99%
“…In a small-size pilot study, patients with pulmonary arterial hypertension-associated systemic sclerosis tolerated DMF poorly and did not provide power to suggest efficacy. Still, authors suggest that Nrf2 remains a valid therapeutic target and should be tested in future trials by using better Nrf2 agonists [ 128 ].…”
Section: Therapeutic Options In Htnmentioning
confidence: 99%
“…Regrettably, a double-blind, randomized, placebo-controlled trial demonstrated that SSc-PAH patients tolerated DMF poorly, and nonsignificantly reduced decline in 6-minute walking distance was found after 24 weeks of DMF treatment (-7.07% vs. -14.97%). Large sample clinical trials need to be conducted to further evaluate the tolerance and efficacy of DMF in PAH [ 97 ]. Muralidharan and his colleagues successfully designed advanced inhalable dry powders containing DMF for targeted delivery to the lungs using particle engineering design technology.…”
Section: Nrf2 Activators As a Novel Therapeutic Approach For Phmentioning
confidence: 99%